Bibliometric Analysis on Street Network components in Influencing Genome of Urban Morphologies - Mohd Nor, Marina; Mohd Noor, Norzailawati; Asmawi, M. Zainora (Journal of Architecture, Planning and Construction Management, 2021)
The bibliometric is a type of research method used in library and information science. The objective of the study are to overview the influences of street network elements comprises of street hierarchy , permeability and urban streetscapes in studying genome of urban morphologies. The quantitative analysis and statistic was used to describe a pattern of publication in the given body of literature. The publications from Scopus and Web of Science were compiled and anlyzed further. The finding shows that, the genome of urban morphologies have being influenced by the street network components nalemy street hierarchy, permeability and legibility, streescapes and pedestrian movement. These components were mutually present in the urban morphology genome which have the capability in accelerating the movement of city. Street hierarchy shows that hierarchical street becomes an organism that vital for the city’s development. The transition of hierarchical system of street contribute to the changes or evolution of the city from time to time. Meanwhile, permeability is represent the image of city. The physical and visual of image of a city is important to bring the city into global level. However, inconsistency of implementation of permeability element will provides a negative impact on the place. Urban streetscape is essential to avoid negative impression of the city images where it should provide visual richness to the city. Lastly, the pedestrian accessibility attract the movement of publis space with the integration of street network. In conclusion, the street network components mutually influenced the morphology of the city over time and become a backbone for the city to reflects the urbanization process. However, based on the bibliometric analysis, the study of street netwok morphology is not grasp sufficent attention from the Asian country.